Hubungan Sosialisasi Gizi Dengan Peningkatan Pengetahuan Tentang Pencegahan Obesitas Pada Balita - Purnamasari, Vivien Dwi (Universitas Pekalongan, 2020)
Currently over nutrition and obesity are epidemics in developed countries, such as UK, Brazil, Singapore and are rapidly developing. The World Health Organization (WHO) noted, in 2005, globally there were about 1.6 billion adults who were overweight or overweight and 400 million of them were categorized as obese. In 2015, it is predicted that obesity cases will double from that number. This study aims to determine the increase in public knowledge about obesity in toddlers. This study used a quasi experimental design with one group pretest and posttest designs. Data collection began on January 9, 2020 in Sumberasih Village, Kediri Regency, with 35 respondents attending the posyandu activities. Of the 35 respondents, it was found that most of the mothers aged 26-30 were 12 respondents, 19 respondents had graduated from high school / MA and 14 respondents did not work. Most of the mother's level of knowledge at the pre-test was in the poor category as many as 13 respondents, while at the time of the post-test with the good category it was 23 people (65.7%). There is a relationship between the socialization of nutrition and increased knowledge about the prevention of obesity under five. Keyword: Education, level of knowledge, obesity